(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In our country, there is a common climate in the population, especially in children, with widespread infectious intestinal diseases. V state predstavleny svedeniya o techenii and prophylactica diarrhoeic disease in children, kotoraya otnositsya k chislu infectious intestinal diseases.